2009
DOI: 10.1007/s10298-008-0357-4
|View full text |Cite
|
Sign up to set email alerts
|

Propriétés antimicrobiennes et toxicité par détermination de la DL50 de l’huile essentielle de Prangos asperula Boissier

Abstract: Cette recherche concerne l'étude des propriétés antimicrobiennes de l'huile essentielle d'une plante sauvage, Prangos asperula Boissier, et de la détermination du seuil de sa toxicité.Les propriétés antimicrobiennes ont été étudiées sur cinq germes :-Streptococcus fecalis, Staphylococcus aureus (bactéries gram +) ; -Salmonella typhi, Escherichia coli (bactéries gram -) ; -Candida albicans (levure). La toxicité de cette huile essentielle a été évaluée à partir de plusieurs expérimentations sur des souris testée… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Serial doses of 25, 50, 75, 100, 150 and 350 mg/mL of PSEO diluted in Tween 80 (1% v/v), as described by Hilan et al (2009), were administrated by intraperitoneal injection to 6 groups in a proportion of 0.01 mL/g of mice body weight. One group, served as vehicle control, received…”
Section: Determination Of the Median Lethal Dose (Ld 50 )mentioning
confidence: 99%
See 1 more Smart Citation
“…Serial doses of 25, 50, 75, 100, 150 and 350 mg/mL of PSEO diluted in Tween 80 (1% v/v), as described by Hilan et al (2009), were administrated by intraperitoneal injection to 6 groups in a proportion of 0.01 mL/g of mice body weight. One group, served as vehicle control, received…”
Section: Determination Of the Median Lethal Dose (Ld 50 )mentioning
confidence: 99%
“…2). The LD 50 is crucial for the prediction of the symptomatology of poisoning after acute overdosing in humans (Hilan et al, 2009). It was demonstrated that intraperitoneal LD 50 values for anethole, major compound in PSEO, were ranged between 650 and 1410 mg/kg in mice.…”
Section: Acute Toxicity Study Of P Saxifraga Essential Oilmentioning
confidence: 99%
“…Five groups were formed, each containing six mice. The first group received physiological saline solution orally (control -), and the other groups were treated with various concentrations of the methanolic extract (600, 1000, 2000, 4000 mg/kg), which were then observed for 72 hrs for toxicity symptoms and mortality rate 17 .…”
Section: Acute Toxicitymentioning
confidence: 99%
“…There are also other biological factors, including death, and the starting date, time and degree of survival recovery are important in toxicity evaluation (Chinedu, Arome, & Ameh, 2013). According to (Hilan, Bouaoun, Aoun, Sfeir, & Garabeth, 2009), the value of LD50 in relation to the concentration of injected essential oil of P. asperula, was analyzed from the straight line defining the death rate, which was approximately 1,05 µL/g. While, the LD50 of the Osthole (7-methoxy-8-(3-methyl-2butenyl)-2H-1-benzopyran-2-one) was 710 mg/kg, which isolated from the root of Prangos ferulacea (Yalda Shokoohinia et al, 2017).…”
Section: Toxicity Of Prangos Towards Animalsmentioning
confidence: 99%